Does the Origin of Parental Acculturation Influence Child's Development - Cieślik, Joachim; Kosińska, Magdalena (Anthropological Review, 1993)
The purpose of this paper is to analyse the influence of parents' culturgenes on stature and body weight of children distinguished by the origin of parental acculturation.